6.3 Tobacco, Smoking Control and Health Education 2016
DOI: 10.1183/13993003.congress-2016.pa4320
|View full text |Cite
|
Sign up to set email alerts
|

Early spirometric changes in asymptomatic smokers; is it a time dependent?

Abstract: Spirometry is the most widely used lung function test both in the diagnosis and stratification of severity of lung disease. The Forced Expiratory Flow between 25 and 75% of the FVC (FEF25_75) is one of the most commonly cited measures of small airways pathology. This study aimed at evaluation of early effect of smoking on small airways. It included: 50 asymptomatic smokers (Group 1) and 50 non smokers (Group 2) as a control. The result revealed: The subjects age was ranged from 18 to 75 years with mean age 43.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Mid-expiratory flows have not yet been shown to be predictive of COPD. Part of the problem may be due to its high within- and between-individual variability, and its high prevalence of abnormality in smokers [ 14 , 15 ] most of whom do not develop COPD as currently defined by FEV/FVC. In contrast, imaging measures of small airways disease, lung clearance index, diffusing capacity for carbon monoxide, airway wall thickening and emphysema predict greater loss of FEV1 [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mid-expiratory flows have not yet been shown to be predictive of COPD. Part of the problem may be due to its high within- and between-individual variability, and its high prevalence of abnormality in smokers [ 14 , 15 ] most of whom do not develop COPD as currently defined by FEV/FVC. In contrast, imaging measures of small airways disease, lung clearance index, diffusing capacity for carbon monoxide, airway wall thickening and emphysema predict greater loss of FEV1 [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decreased pulmonary function tests (PFT) in smokers were established to be statistically significant for FEF 25-75% with no significant difference in other values. Mistry et al [14] they reported that at every age group, smokers had decreased FEV1/FVC ratio making them prone to develop COPD in the future. Nawafleh et al [15] and.…”
Section: Discussionmentioning
confidence: 99%